Depiction of heaven and hell in “Divani Hikmet” by Yasawi and «Divine Comedy» by Dante - Aimukhambet , Жанат (Turkic Studies Journal, 2023)
The aim of the paper is a comparative analysis of the verbal aitys of heaven and hell in the «Divani Hikmet» by Khoja Ahmed Yasawi with samples of aitys characteristic of the Turkic verbal art, as well as with the description of heaven and hell in the «Divine Comedy» by Dante Alighieri. The spiritual, philosophical and artistic value of Yasawi’s Hikmet is considered, and the concepts of heaven and hell in the consciousness of mankind are studied. It is religiously justified in the sacred scriptures that a soul in the afterlife falls into one of two worlds, depending on its actions in this world. The image of heaven and hell became the basis of sacred books and works of art. Yasawi provides great humanistic ideals, providing a controversy between heaven and hell. The fact that a person’s moral existence is assessed by conscientiousness, as well as the principles of spiritual value are most clearly expressed in the text of verbal competition. The purpose of aitys is to defeat the opponent with meaningful words. Hikmet takes the form of aitys as a genre in harmony with the Turkic verse in content and form, and an effective way of conveying thoughts.